Qatar : Selected Issues. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2015)
This Selected Issues paper discusses strengthening of fiscal policy and fiscal frameworks in Qatar. It proposes ways to ensure that sustainable fiscal policy is maintained in the medium to long term in Qatar. Fiscal policy remains sustainable, but given the large drop in oil prices, revenue-raising and expenditure-containing measures need to be considered to ensure intergenerational equity. Measures aimed at containing current spending, prioritizing capital expenditure, and raising nonhydrocarbon revenues would help bring fiscal policy back to consistency with intergenerational equity. Strengthening fiscal frameworks would help achieve the desirable fiscal policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet